The Role of Serverless Architecture in Scalable and Efficient Web Development (International Journal of Scientific Research in Science and Technology, 2025)
Web development has been transformed by serverless computing, which provides scalable, economical, and effective cloud-based solutions. Developers can concentrate entirely on developing code thanks to serverless architecture, which removes the need to manage real servers. This paradigm transfers the operational load to cloud providers, who take care of security, scalability, and infrastructure maintenance. But even with its benefits, issues with security, performance delay, and vendor lock-in still exist. To overcome these obstacles, developers must use best practices, such as enhancing cold start performance and putting robust security measures in place. This essay examines the development of serverless computing, as well as its advantages, difficulties, and potential applications. It also analyzes real-world use examples that demonstrate the revolutionary potential of serverless architecture across a range of industries, including e-commerce, banking, and healthcare, and offers suggestions for effective implementation.